Scouting-based approach to strengthen social care character in elementary students' extracurricular activities - Putra, Ilzam Alfadila; Wakhudin, Wakhudin (Indonesian Research Journal in Education |IRJE|, 2026)
This study investigated the strategic role of scouting extracurricular activities in strengthening the social care character of elementary students at SD Negeri Karanglo, Banyumas. Addressing challenges in character education, this research employed a descriptive qualitative approach, collecting data through observation, interviews, and documentation. The findings revealed that structured scouting activities such as camping, community service, and collective tasks function as a "moral laboratory" where students engage in real-life value internalization. The process involves habituation, reflection, and guided social action. Teachers act as moral models, facilitators, and emotional guides throughout the process. These efforts align with the Pancasila student profile. They are supported by Vygotsky's social constructivism and Kohlberg's theory of moral development. The study concludes that scouting is a practical and contextual strategy for instilling social care values and recommends further improving teacher training and facilities to enhance the program's impact in elementary education.